(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Postoperative cognitive dysfunction greatly affects the quality of recovery after surgery, especially in the elderly, prolonging hospital stay. To reduce anxiety and stress for patients who are anesthetized with spinal anesthesia using sedation. Therefore, we hypothesized that the use of midazolam sedation during surgery is related to postoperative cognitive dysfunction in elderly patients following joint arthroplasty. Objective: Determine the relationship between midazolam and cognitive disorders after joint replacement surgery in the elderly. Materials and Methods: Elderly patients (≥ 60 years) receiving spinal anesthesia for joint arthroplasty. Design of this study is longitudinal observational, prospective, single-center. Results: 22,5% of elderly patients had postoperative cognitive dysfunction for joint arthroplasty and received spinal anesthesia in the first 5 days of surgery. Elderly patients with postoperative cognitive dysfunction have a longer postoperative treatment (p < 0.05). Multivariable Cox regression analysis noted that using of sedative midazolam during surgery (p=0,002) was a risk factor for postoperative cognitive dysfunction. Conclusions: Of all the 107 patients, we noted that elderly patients with postoperative cognitive dysfunction have a longer postoperative treatment. The use of sedative midazolam during surgery is a risk factor for postoperative cognitive dysfunction.